KEPUASAN NASABAH SEBAGAI MEDIATOR ANTARA KUALITAS PELAYANAN BANK DAN TINGKAT LOYALITAS NASABAH - IMELDA SITINJAK (JURNAL ILMIAH KOHESI, 2018)
This study aims to determine the role of customer satisfaction as a mediator between the influence of the service quality of bank to customer loyalty. The object of this research is Putri Hijau Medan Branch of Bank Rakyat Indonesia. This research is motivated by the increasing number of BRI customers of Putri Hijau Medan Branch which closed the account for 3 years. A purposive method has been selected to obtain the required data in this study. This study took 110 respondents and all respondents were BRI customers of Putri Hijau Medan Branch. Data analysis was using Structural Equation Model with Lisrel computer program. The result of this research concludes that there is no influence of service quality directly which is significant to customer loyalty (H1 rejected). But indirectly there is a significant effect of service quality on customer loyalty that is when customer satisfaction is determined as mediator (H2 accepted). This is supported by the significant effect of service quality on customer satisfaction (H2a received), and customer satisfaction on customer loyalty (H2b accepted). The results of this study have an implication for the academic that is strengthening the justification of previous research that customer satisfaction mediate the relationship between service quality and customer loyalty. In addition, this research expands the object of research in banking, especially in Bank BRI. While the managerial implication is the leader and all employees of Bank should prioritize customer satisfaction in serving customers.